(untitled) (Revista Electrónica REDINE, 2018)
The school trains people who can live together in a climate of respect, tolerance, participation and freedom, capable of integrating knowledge and ethical and moral valuation, who are citizens respectful of the legal norms that will strengthen their social participation, a primary challenge for the countries with democratic systems. The objective of this research is to interpret the implications of the social responsibility of the school in the construction of citizenship. It is based on the theoretical approaches on morals, ethics and social responsibility of the Venezuelan researchers Gómez (2005, 2008) and Guédez (2002, 2006); on principles and leadership of Covey (2002) and Senge (1993); on education by Berguer, Luckman (1968) and Morín (2002). The methodology is approached from an ethnographic orientation within the interpretive approach. Unstructured, open and flexible interviews were conducted with teachers and directors of Basic Education of the National Education Unit "Tomás Liscano" of Quíbor, Jiménez Municipality of Lara State. From the analysis of the stories emerge the categories of analysis: Student Socialization, Teacher Ethics, School Social Participation. As a final non-final reflection I infer: the school is the center of socialization par excellence, students are the object of the processes of internalization, objectification and legitimization of the social order, from which the norms and values ​​of their culture are transmitted, in accordance to individual and collective interests; the crisis of values ​​of the current Venezuelan society provokes an ethical rupture in the teachers: inconsistency between saying and doing, under commitment with the school and lack of responsibility with the community; Many have declined in their role as educators of citizens based on universal values, an obligation of the Venezuelan State.